2000
DOI: 10.1093/humrep/15.3.650
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine polyps—a cause of unscheduled bleeding in women using the levonorgestrel intrauterine system: Case Report

Abstract: The levonorgestrel intrauterine releasing system is a contraceptive that has been shown to reduce menstrual blood loss dramatically. Breakthrough bleeding, however, is a relatively common occurrence as with all methods of progestogen-only contraception and this limits its acceptability for women. Amenorrhoea can be achieved in the majority of women within 12 months of insertion. Any new pattern of bleeding after amenorrhoea or a persistence of heavy bleeding may be due to co-existing intrauterine pathology suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…The irregular appearance of the endometrial surface with polyploidal structures suggest that these micropolyps may contribute to the bleeding patterns observed following exposure to LNG-IUS. This view is supported by the hysteroscopic observations of one group (Brechin et al, 2000), who reported the presence of polyps in three women exposed to LNG-IUS, and also that the bleeding problems resolved after surgical removal of these polyps. The presence of unscheduled breakthrough bleeding and reduction in menstrual blood loss suggests that the progestogens might affect the endometrial vascular system directly.…”
Section: Introductionmentioning
confidence: 65%
“…The irregular appearance of the endometrial surface with polyploidal structures suggest that these micropolyps may contribute to the bleeding patterns observed following exposure to LNG-IUS. This view is supported by the hysteroscopic observations of one group (Brechin et al, 2000), who reported the presence of polyps in three women exposed to LNG-IUS, and also that the bleeding problems resolved after surgical removal of these polyps. The presence of unscheduled breakthrough bleeding and reduction in menstrual blood loss suggests that the progestogens might affect the endometrial vascular system directly.…”
Section: Introductionmentioning
confidence: 65%
“…The prevalence of EP in patients with IUD does not seem to have been assessed. Meanwhile, studies have reported cases for ParaGard copper and levonorgestrel IUD [ 121 ], despite therapeutic properties of this latter on endometrial hyperplasia [ 122 ]. The causal relationship between EP and infertility has been confirmed in only one randomized trial [ 102 ].…”
Section: The Concept Of Impaired Inflammatory State Of the Endometriumentioning
confidence: 99%
“…In looking for intrauterine pathology, well-established procedures such as hysteroscopy and saline infusion sonography are indicated. 18 If exceptional bleeding persists for more than 3 months or if the bleeding pattern is altered, an endometrial biopsy and cervical smear are indicated.…”
Section: Treatment Of Menorrhagiamentioning
confidence: 99%